Primary biliary cholangitis: molecular pathogenesis perspectives and therapeutic potential of natural products - Zhao, Yanling; Wei, Shizhang; Chen, Lisheng; Zhou, Xuelin; Ma, Xiao (Frontiers in Immunology, 2023)
Primary biliary cirrhosis (PBC) is a chronic cholestatic immune liver disease characterized by persistent cholestasis, interlobular bile duct damage, portal inflammation, liver fibrosis, eventual cirrhosis, and death. Existing clinical and animal studies have made a good progress in bile acid metabolism, intestinal flora disorder inflammatory response, bile duct cell damage, and autoimmune response mechanisms. However, the pathogenesis of PBC has not been clearly elucidated. We focus on the pathological mechanism and new drug research and development of PBC in clinical and laboratory in the recent 20 years, to discuss the latest understanding of the pathological mechanism, treatment options, and drug discovery of PBC. Current clinical treatment mode and symptomatic drug support obviously cannot meet the urgent demand of patients with PBC, especially for the patients who do not respond to the current treatment drugs. New treatment methods are urgently needed. Drug candidates targeting reported targets or signals of PBC are emerging, albeit with some success and some failure. Single-target drugs cannot achieve ideal clinical efficacy. Multitarget drugs are the trend of future research and development of PBC drugs.